2016
DOI: 10.11648/j.ajee.20160402.11
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Parameters for Biodiesel Production Using Response Surface Methodology

Abstract: Abstract:The effect of five process parameters namely: reaction time, reaction temperature, stir speed, catalyst concentration and methanol-oil ratio on the transesterification process of waste frying oil to biodiesel were investigated. Optimization of the five process parameters and their quadratic cross effect was carried out using a four level-five factor central composite experimental design model and response surface methodology with each factor varied over four levels. Taking the biodiesel yield as the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The effects of the methanol to oil molar ratio and catalyst loading on the CMKO-FAME yield while keeping the reaction time constant are shown in Figure B. As the reaction between reactant methanol and triglycerides of CMKO is reversible in nature, the molar ratio and catalyst loading are important to increase the reaction rate. ,, The two-dimensional (2-D) plots were also employed to explain the interaction between the other two variables. Based on the analysis of variance (ANOVA), the transesterification reaction was significantly affected by various interactions between the process variables (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the methanol to oil molar ratio and catalyst loading on the CMKO-FAME yield while keeping the reaction time constant are shown in Figure B. As the reaction between reactant methanol and triglycerides of CMKO is reversible in nature, the molar ratio and catalyst loading are important to increase the reaction rate. ,, The two-dimensional (2-D) plots were also employed to explain the interaction between the other two variables. Based on the analysis of variance (ANOVA), the transesterification reaction was significantly affected by various interactions between the process variables (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…From Figure B–D, it can be observed that the process variables have significant interaction effects on CMKO-FAME yield. The effect of both the process variables (reaction time and molar ratio) had a positive effect on the CMKO-FAME yield up to the optimal point, after which a further increase in the methanol or catalyst concentration did not increase the CMKO-FAME yield but rather caused a marginal decrease in the CMKO-FAME yield, resulting in the formation of soap and an increase in the cost of the postreaction steps. , The surface and contour plots show the relationships between the variables during their interaction. Each contour curve presents the effect of two variables on the CMKO-FAME yield, holding the third variable at a constant level.…”
Section: Resultsmentioning
confidence: 99%
“…The design of the numerical experiment was carried out using the Response Surface Methodology (RSM) and the Central Composite Design (CCD) in order to determine the feasible combinations of process parameters and the significance of each as well as effects of their interactions on the cutting force. The RSM is a mathematical and statistical technique usually employed for numerical modelling of numerical experiments in order to determine the optimum process condition and the influence of process parameters on the output response and to determine the optimum condition [Bello et al, 2016]. The ranges of the process parameters are cutting speed (250-280 mm/min), feed per tooth (0.06-0.24 mm) and axial depth of cut (0.30-3.0 mm) are varied over four levels while cutting force serves as the response of the designed experiment.…”
Section: The Design Of the Numerical Experimentsmentioning
confidence: 99%
“…This indicates the effectiveness of the lipase enzyme being utilized in the minimum amount. Previous studies reported that the yield was improved as the amount of enzyme was increased in the reaction system (Silitonga et al 2016;Bello et al 2016;Al-Zuhair 2005).…”
Section: Effect Of Parametersmentioning
confidence: 99%